PEMANFAATAN TEKNOLOGI AEROPONIK BERBASIS PRECISION AGRICULTURE DALAM OPTIMALISASI RANTAI PASOK BENIH KENTANG G-0 PADA KELOMPOK TANI DI KABUPATEN AGAM - Deperiky, Dedet; Febrianto, Hary; Yoga, Trio Candra (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2023)
Potato production in West Sumatra has decreased from 2015-2018. One of the factors causing the decline in potato production is because local farmers have not been optimal in producing G0 potato tuber seeds, still using conventional methods, so to meet the need for G0 potato tuber seeds, farmers buy them from outside the region. Efforts that can be made to increase seed production are by utilizing technology in the agricultural sector such as aeroponic systems. Aeroponics is a farming activity carried out by hanging plant roots in a container where the plant roots then receive water and nutrients through spraying in the form of mist droplets. The aim of the research is to design and create an aeroponics system that can work automatically to maintain the concentration of the solution and the availability of water in the box container so that it can meet the nutritional needs for potato plant growth. This research starts from functional design, structural design, control system design, calibration, technical testing and analysis. The performance of the total dissolved solid (TDS) sensor during the 10 week study obtained an error value of 7.398% and an accuracy level of 92.602% with an average range of TDS sensor reading values of 1,142,000 ppm – 1,358,333 ppm. Meanwhile, the performance of the HC-SR04 sensor obtained an error value of 1.300% and an accuracy level of 98.700% with a range of reading values for the HC-SR04 sensor, namely 12 cm – 26 cm. The results of observations of plant growth in the form of plant height showed that the average plant height at week 13 was 42.175 cm/stem, the average number of leaf stalks was 14.8 stalks. The number of tubers produced by the aeroponic system is 14,850 tubers/stem, which is more than the conventional method, namely 5-7 tubers/stem. The aeroponic system can work well because the aeroponic system is able to maintain the concentration of the solution according to plant growth needs (1,050 ppm - 1,400 ppm) and the system can maintain the availability of water in the box container.